Perencanaan Penataan Ruang Desa Berbasis Potensi Desa sebagai Kendali Pembangunan Desa yang Terarah dan Berkelanjutan: Village Spatial Planning Based on Village Potential as a Directed and Sustainable Village Development Control - Agustina Rohiani (P4W LPPM IPB, 2021)
West Java province is currently active conducting development in rural areas in order to improve the welfare of its community through the improvement of IDM (Indeks Desa Membangun/Village Index Development). In general, village development has not been based on village spatial plan, resulting it less optimal and not synergized with Regency’s Mid-term Development Plan (RPJMD Kabupaten). Therefore, each village government shall first conduct village spatial planning as the basis for preparation of Village Mid-term Development Plan (RPJM Desa), in order to understand its potentials and development plans that exist in its area and realize the importance of village spatial planning. This research uses qualitative and comparative descriptive methods. The existence of the Village Spatial Plan (RTRW Desa) enables village development to become more synergistic, directed, and sustainable, suppresses conflict of interests, controls the use of space in village area to remain in accordance with its function and designation, hence the level of environmental damage can be minimized. Village spatial planning is new to village governments and no guidelines exist yet. Thus, the central or local government shall prepare guidelines for village spatial planning and conduct socialization and education.